Being Occupied in the Everyday - Wright-St Clair, VA; Smythe, L (AUT University, 2012)
This chapter draws on the stories told by elder New Zealanders as a way of illuminating the deeply contextual, habitual, relational and precarious nature of engaging in everyday occupations. In the telling we hear how routines matter because they give shape and structure to a day. Having a purpose, however, calls one into engaged activity with enthusiasm. Everyday occupations offer connectedness in time and with others. They can give a sense of continuity which stretches back into the distant past and which projects forward into the future. Memories and deeply held social customs matter. As such, those important to one‟s life who have died still stay as part of the livings‟ relational context. Paradoxically, we also hear how the ordinariness of familiar occupations is the context for the unfamiliar to be made visible. Precariousness is ever-present. These and other complexities of being in the everyday in advanced age, such as aloneness, and intergenerational relationships are analyzed vis-à-vis occupation using both a phenomenological and a transactional perspective. It is only by understanding the holistic, contextual nature of engaging in everyday occupations that one comes to recognize that when working with older people one must sensitively listen and think before acting. A transactional perspective provides the conceptual tools to support this practice.